The effect of starch isolation method on physical and functional properties of Portuguese nut starches. II. Q. rotundifolia Lam. and Q. suber Lam. acorns starches - Correia, Paula Reis; Nunes, Maria Cristiana; Beirão-da-Costa, Maria Luísa (Food Hydrocolloids, 2013)

The effect of starch isolation method on physical and functional properties of Portuguese nut starches. II. Q. rotundifolia Lam. and Q. suber Lam. acorns starches - Correia, Paula Reis; Nunes, Maria Cristiana; Beirão-da-Costa, Maria Luísa (Food Hydrocolloids, 2013)
A new starch was isolated from fruits of two acorn species, Quercus rotundifolia and Quercus suber by alkaline (A3S) and enzymatic (ENZ) methods and physical and functional properties were studied. The isolation method induced changes in most of those properties in the isolated starches, mainly in resistant starch content, syneresis, pasting, thermal and rheological properties. Isolated acorn starches presented high amylose content (53e59%) and resistant starch content (30.8e41.4%). Acorn starches showed limited and similar solubility values and swelling power values, showing a gradual increase from 60 C to 90 C. The pasting temperatures ranged from 67.5 to 72.0 C and pastes did not present breakdown, which is suggestive of a high paste stability of acorn starches during heating. At ambient temperature the turbidity and syneresis values were low, but when held at freezing temperatures the syneresis signiﬁ- cantly increased. Thermal analysis revealed that the acorn starches easily undergo transition phenomena as shown by the low To and enthalpy values (4.1e4.3 J/g), these effects were more evident in starches isolated by ENZ method. Pastes are more elastic than viscous and form strong gels after cooling. Q. suber starch was shown to be more sensitive to the effect of isolation method. Generally, starch isolated by enzymatic method presented less interesting functional properties, since this isolation procedure greater affected the raw structure of starches
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: acorns; Functional properties; isolation method; rheological properties; starch; thermal properties

Starch isolation from chestnut and acorn flours through alkaline and enzymatic methods - Correia, Paula Reis; Beirão-da-Costa, Maria Luísa (Food and Bioproducts Processing, 2012)
Two different procedures were used to isolate chestnut (Castanea sativa Mill.) and acorn (Quercus suber) starch. Starch was extracted from the ﬂour of these dried fruits by: (i) low shear at alkaline pH and successively using three sieves (A3S) at different centrifugation conditions (velocity and time) and (ii) enzymatic treatment at low shear (ENZ) at a different amount/digestion time of protease. In both cases a Central Composite Rotatable Design (CCRD) was used as an experimental design. Results were treated through the Response Surface Methodology (RSM). Based on maximum yield values and the degree of purity, the best modiﬁed conditions encountered were applied in a new trial and mass balance was established for both isolation procedures. The best centrifugation conditions encountered for the A3S isolation method were 800 × g during 15min, and for the ENZ method 900 units of protease despite the incubation time, for the same centrifugation terms. The yields reached with these experimental conditions for the A3S and ENZ methods were 83.9% and 79.9% for chestnut and 88.5% and 86.9% for acorn, respectively. Isolated starches shown to be higher in purity, presented values of 98.3% and 96.3% for chestnut and 98.1% and 97.6% for acorn, respectively for the A3S and ENZ methods
The following values have no corresponding Zotero field: publisher: Institution of Chemical Engineers
Keywords: acorn; chestnut; composition; isolation method; starch; yield

Chestnut and acorn starch properties affected by isolation methods - Correia, Paula Reis; Beirão-da-Costa, Maria Luísa (Starch - Stärke, 2010)
Starches from chestnut (Castanea sativa Mill.) and acorns (Quercus suber Lam. and Q. rotundifolia Lam.) were isolated from dried fruits using four different methods. These involved a physicochemical and/or an enzymatic treatment followed by centrifugation and sieving: (i) low shear at alkaline pH – LSA, (ii) high shear in water – HSW, (iii) enzymatic treatment at low shear – LSE, (iv) LSA and using successively three sieves – LSA3S. Raw yield, purity, colour parameters, morphology, protein, fat, ash, reducing sugars and amylose contents, damaged starch content and viscoamylographic proﬁles were studied in isolated starches, presenting different properties through different methods. In general, chestnut starch seems to be poorly resistant to extraction methodologies as shown by the damaged starch content and viscoamylographic properties encountered during this study. Moreover, acorn starches exhibited cross-linked amylographic patterns. For all the tested raw materials, the LSA3S isolation method always higher yield and purity of starches. Gelatinization temperature and peak consistency were also higher than those shown by starches produced by the other methods, a less damaged structure was also evident. In conclusion, it seems that this method is the most suitable to produce starch for food ingredient usage.
Keywords: acorn; chestnut; morphology; physicochemical properties; starch isolation methods